Un fantasma recorre América: el fantasma de la sincronía - Edgardo Dobry (Cuadernos LIRICO)
T.S. Eliot, Lugones, Borges, Lezama Lima, Alfonso Reyes and Haroldo de Campos are some of American writers who, throughout the 20th century, and with diverse but associated modulations, formulated the complex relationship between American literatures and Western tradition. Against the axis of continuity and chronological succession with which literary history works, the new concept of tradition proposes the simultaneous existence of works that are related to each other, even if they belong to different literatures and historical periods.